The Influence of Social Media Influencers, Content Marketing Strategy and Trust on Interest in Using Sharia Fintech - Ilham Akbar; Faishal Rahimi; Zulfikri Akramul Akbar (IJSM, 2026)
This study aims to analyze the influence of social media influencers, content marketing strategies, and trust on the intention to use Islamic Fintech in Central Java, with a case study on Amanah Pay Syariah users. The growing penetration of Sharia-based Fintech platforms in Indonesia highlights the need to understand the digital marketing factors influencing consumers’ intentions to adopt ethical financial technology. This research applies a quantitative approach using a survey design of 150 active Islamic Fintech users. Data were collected through online questionnaires with a 5-point Likert scale and analyzed using multiple linear regression with SPSS version 26. The results show that social media influencers have a positive and significant effect on the intention to use Islamic Fintech. Content marketing strategy also has a positive and significant influence on user intention. Furthermore, user trust plays the most dominant role in encouraging people’s decisions to use AmanahPay Syariah services. These findings emphasize the importance of ethical and consistent digital communication strategies to build trust and strengthen the adoption of Sharia-based financial technology services.